SOCIAL RESPONSIBILITY OF UKRAINIAN UNIVERSITIES: COMPARATIVE ANALYSIS AND MAIN DIRECTIONS OF DEVELOPMENT - O. Grishnova; S.Bekh (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
The paper encapsulates the essence of university social responsibility. The study explores basic directions of universities social responsible activities in Ukraine and in western countries. A comparative assessment is conducted as to distribution of social responsibility in national universities activities. The paper specifies priority areas of social responsibility education.